Changes in biooxidation mechanism and transient biofilm characteristics by As(V) during arsenopyrite colonization with Acidithiobacillus thiooxidans. (1st August 2018) - Ramírez-Aldaba, Hugo; Vázquez-Arenas, Jorge; Sosa-Rodríguez, Fabiola S; Valdez-Pérez, Donato; Ruiz-Baca, Estela; Trejo-Córdoba, Gabriel; Escobedo-Bretado, Miguel A; Lartundo-Rojas, Luis; Ponce-Peña, Patricia; Lara, René H
Abstract: Chemical and surface analyses are carried out using Raman spectroscopy, X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM–EDS), atomic force microscopy (AFM), confocal laser scanning microscopy (CLSM), glow discharge spectroscopy (GDS) and extracellular surface protein quantification to thoroughly investigate the effect of supplementary As(V) during biooxidation of arsenopyrite by Acidithiobacillus thiooxidans . It is revealed that arsenic can enhance bacterial reactions during bioleaching, which can strongly influence its mobility. Biofilms occur as compact-flattened microcolonies, being progressively covered by a significant amount of secondary compounds (S n   2-, S 0, pyrite-like). Biooxidation mechanism is modified in the presence of supplementary As(V), as indicated by spectroscopic and microscopic studies. GDS confirms significant variations between abiotic control and biooxidized arsenopyrite in terms of surface reactivity and amount of secondary compounds with and without As(V) (i.e. 6 μm depth). CLSM and protein analyses indicate a rapid modification in biofilm from hydrophilic to hydrophobic character (i.e. 1–12 h), in spite of the decrease in extracellular surface proteins in the presence of supplementary As(V) (i.e. stressed biofilms).